Academic E-learning in Poland Results of a Diagnostic Survey - Maleńczyk, Izabela; Gładysz, Bartłomiej (International Journal of Research in E-learning, 2019)
Academic e-learning is not a new phenomenon world-wide or in Poland. However, there are only a few publications examining academic e-learning in Poland from a wider perspective (i.e., country-wide, and not only from that of the specific course, faculty member, or university orientation), and none of them present complex analysis and diagnosis. The goal of this paper is to present an investigation of academic e-learning in Poland in both public and private universities. The sample of 139 universities was surveyed, and relations between variables – such as e-learning process characteristics and university characteristics – were analysed via hypotheses testing. Results of the survey may constitute a basis for comparison on a national and international level and offer strategic directions for university authorities.